InoStylish Pen / Halawati Wahab … [et al.] - Wahab, Halawati; Mohamad, Noor Hidayah; Ahmad, Noorlizawati; Ahmad Fauzi, NorAfifah; Hamzah, NurJariyah (2018)
Initial observation was done among University students, which include the Institusi Pengajian Tinggi Awam (IPTA) and Institusi Pengajian Tinggi Swasta (IPTS), our team has developed an improvement on an existing product for contributing to them. The product to be marketed by our company is InoStylish Pen.